Conditions for self-ordering of porous structure of anodic aluminum oxide in weak and strong acids. (20th January 2019) - Mirzoev, R.A.; Davydov, A.D.; Vystupov, S.I.; Kabanova, T.B.
Abstract: The model, which under certain assumptions enables one to predict the conditions for self-ordering of porous anodic oxide film (AOF) on aluminum in the weak and strong acids, is proposed. The work is a development of the theory of concentration changes in the growing oxide pores proposed by Patermarakis et al. The most important difference from the theory is the consideration of the second-stage dissociation of strong acids. The problem of the conditions of self-organization of porous AOF on aluminum is solved analytically. The critical porosity Ps and the corresponding anodizing voltage Vr that provides the optimal self-organization of porous structure of AOF are interpreted. Close values of Vr and the breakdown voltage VBP are explained. Using the model, the critical porosity Ps for solutions of weak monobasic acids and strong dibasic acids with low second-stage dissociation constant is calculated and the effect of various factors on the critical porosity Ps is determined. The obtained results give an answer to the question why all activating anions, which cause pitting dissolution, are the anions of strong monobasic acids.